Increase in the Acceleration Efficiency of Solids in a Hybrid Coaxial Magnetoplasma Accelerator; Journal of Applied Mechanics and Technical Physics; Vol. 59, iss. 1 - Gerasimov D. Yu. Dmitry Yurievich (2018, 2018)
Title screen